Serotyping of pasteurella multocida based on capsules in ducks in Kelantan, Malaysia - Md. Zahirul Islam Khan; Imad Ibrahim Ali Al-Sultan; Mohd Mokhtar Bin Arshad; Erkihun Aklilu Woldegiorgis; Nani Izreen Binti Mohd Sani
The present study was carried out on 65 duck liver to investigate the serotypes of Pasteurella multocida causing fowl cholera in the state of Kelantan, Malaysia. These samples were obtained from different farms in Kelantan which was preparing for marketing purpose during the period from August to December 2013. Bacterial isolation, morphological identification, biochmical properties, and bacterial DNA extration for PCR revealed that out of 65 samples 4 were P. multocida positive, confirmed by PCR. The 4 samples identified produced species-specific 460bp band with KMT1T7 and KMT1SP6 primers.PCR serotyping using CAPA-FWD and CAPA-REV primers revealed that among 4 P. multocida positive samples, 1 was type A strain having 1044 bp, and the other 3 strains were untypeable. The present study revealed that P. multocida type A strain is prevalent in Kelantan.